Orchids as Potential Sources of Anticancer Agents: Our Experience - Pant, Bijaya; Paudel, Mukti Ram; Joshi, Pusp Raj (Annapurna Journal of Health Sciences, 2023)
Cancer is the second leading cause of death globally and the cancer burden continues to grow, exerting tremendous physical, emotional and financial strain on individuals, families, communities and health systems. Many health systems in low- and middle-income countries are ill-prepared to manage this burden, and around the world large numbers of cancer patients do not have access to timely quality diagnosis or treatment. Natural products, especially originated from plants, have been applied as remedies to treat various diseases, including cancer, for thousands of years. Several anticancer agents derived from plants, such as paclitaxel (taxol), vinblastine, vincristine, camptothecin derivatives, podophyllotoxins, are in clinical use and a number of other promising agents are in preclinical or clinical development. A growing number of bioactive compounds with cytostatic and cytotoxic activities to treat cancer have been isolated from several orchid species. The Annapurna Research Center in collaboration with other academic institutions is engaged in identifying and exploring anticancer compounds in orchids of Nepal. The center has identified ten different orchid species which contain high phenol and flavonoid contents evidently showing anticancer activities in our in vitro assays against different cancer cell lines viz cervical cancer, lung cancer and brain tumor cell lines. These findings demonstrate that orchids which have been used in in various formulations in traditional medicine since ancient times qualify as potential source for novel drug candidates or starting points for further lead optimization towards clinical candidates for the most urgently needed treatment of aggressive types of cancer. This review paper highlights that in all likelihood; our contributions in orchid research here in Nepal could bring great relief to patients with cancer globally.